2016
DOI: 10.1007/s10508-016-0724-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexist Attitudes Among Emerging Adult Women Readers of Fifty Shades Fiction

Abstract: Stereotypical sexist representations of men and women in popular culture reinforce rigid views of masculinity (e.g., males as being strong, in control, masterful, and aggressive) and femininity (e.g., women as being fragile and weak, unassertive, peaceful, irrational, and driven by emotions). The present study examined associations between the fictional series Fifty Shades-one popular culture mechanism that includes pervasive traditional gender role representations-and underlying sexist beliefs among a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, previous studies identified a link between women's benevolent sexism and exposure to erotica in which a man sexually dominates his female partner, whipping, spanking, and tying her up (Harris, Thai, & Barlow, 2016). After reading male-dominance erotica, women expressed significantly higher benevolent sexism compared to men (Harris et al, 2016), and were especially likely to endorse benevolent sexism if they rated erotica in which a man dominates a woman as ''romantic'' (Altenburger, Carotta, Bonomi, & Snyder, 2016). Thus, these studies suggestthata benevolentlysexistworldviewis associated with attitudes that limit women's sexual expression and endorse men's sexual dominance.…”
Section: Benevolent Sexismmentioning
confidence: 92%
“…Furthermore, previous studies identified a link between women's benevolent sexism and exposure to erotica in which a man sexually dominates his female partner, whipping, spanking, and tying her up (Harris, Thai, & Barlow, 2016). After reading male-dominance erotica, women expressed significantly higher benevolent sexism compared to men (Harris et al, 2016), and were especially likely to endorse benevolent sexism if they rated erotica in which a man dominates a woman as ''romantic'' (Altenburger, Carotta, Bonomi, & Snyder, 2016). Thus, these studies suggestthata benevolentlysexistworldviewis associated with attitudes that limit women's sexual expression and endorse men's sexual dominance.…”
Section: Benevolent Sexismmentioning
confidence: 92%
“…In addition, hetero-leathermen and hetero-leatherwomen have distinct experiences effected by the overlapping dynamics that can take place in leather and S/M erotic play. In particular, heterosexual women with leather and S/M interests are increasingly situated in a sexist and misogynistic framework emerging out of both the inaccuracies of the Fifty Shades series as well as some cultural aspects unique the hetero-leather community (Altenburger et al 2017;Deller and Smith 2013;Green 2015;Smith, 2015;Sprott and Berkey 2015;Yost 2010). Together, these dynamics can reinforce problematic perspectives about women among hetero-leathermen.…”
Section: Hetero-leather Culturementioning
confidence: 99%
“…In addition, the current study focused exclusively on leathermen due to a lack of leather-identified respondents of other genders in the study sample. 3 As others have noted (Altenburger et al 2017;Breslow, Evans, and Langley 1985;Deller and Smith 2013;Green 2015;Smith, 2015;Sprott and Berkey 2015), women's interests in leather and/or BDSM can have important implications for understanding their own attitudes toward women and sexist perspectives. In addition, though there were interesting findings related to the sociodemographic controls in the regression models, a sizable percentage of the leathermen subsample was White (63%), a majority were from a suburb or large city (69%), and most reported some college education (88%).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Not only has research demonstrated that language reveals information about romantic interest, but that the language used in romantic literature captures human, and specifically, women's, love preferences. Researchers have found that women who enjoy romance novels with traditional gender roles will report aligning with sexist beliefs more so when compared with others (Altenburger, Carotta, Bonomi, & Snyder, 2017). Considering that language can be examined to predict the likeliness of attraction, romantic initiation, relationship stability, relationship satisfaction, and romantic preference, it would stand that language can provide insight on relationships and particularly, how women perceive romance.…”
Section: Language Of Lovementioning
confidence: 99%